(untitled) (London Journal of Research In Management & Business, 2024)
The emphasis of theory-based training on application-basedtraining has its importance in the healthcare sector. Relationship building and a patient-centric approach have taken the core area for organizational commitments to improving their services.When the acquisition of the new set of skills by the participants is used in daily tasks, at low cost, in a dynamic format, the theories are achieved by active participation, and it enables the context to be adapted right habits.As a cluster training program, the participants of the soft skill training programhad an opportunity to link with 4 major clusters such as intrapersonal communication, interpersonal communication, adaptability and developing comfort zone and stress management, and risk reduction in communication. This research study provides insights into the training methodology of soft skill competencies for future healthcare professionals. It helps in assessing the effectiveness of the training program by adapting learning by doing methodology. By adapting Northouse & Northouses health communication model, data collected about preparation for the course by the participants, information delivered, and adequacy of inputs provided, Overall rating of the training program conducted as parameters. The research emphasizes the 3 main areas as skill-based learning, tool-based learning, and problem-based learning in the learning-by-doing methodology. This research study provides details on the effectiveness of the training program for communication and soft-skill competencies to be logical, systematic, replicable, focuses on the priority problems, and generative of data that is measurable and action-oriented.